Application of Double-Strand RNAs Targeting Chitin Synthase, Glucan Synthase, and Protein Kinase Reduces Fusarium graminearum Spreading in Wheat - Yang, Peng; Yi, Shu-Yuan; Nian, Jun-Na; Yuan, Qing-Song; He, Wei-Jie; Zhang, Jing-Bo; Liao, Yu-Cai (Frontiers in Microbiology, 2021)
Controlling the devastating fungal pathogen Fusarium graminearum (Fg) is a challenge due to inadequate resistance in nature. Here, we report on the identification of RNAi molecules and their applications for controlling Fg in wheat through silencing chitin synthase 7 (Chs7), glucan synthase (Gls) and protein kinase C (Pkc). From transgenic Fg strains four RNAi constructs from Chs7 (Chs7RNAi-1, -2, -3 and -4), three RNAi constructs from Gls (GlsRNAi-2, -3 and -6), and one RNAi construct from Pkc (PkcRNAi-5) were identified that displayed effective silencing effects on mycelium growth in medium and pathogenicity in wheat spikes. Transcript levels of Chs7, Gls and Pkc were markedly reduced in those strains. Double-strand RNAs (dsRNAs) of three selected RNAi constructs (Chs7RNAi-4, GlsRNAi-6 and PkcRNA-5) strongly inhibited mycelium growth in vitro. Spray of those dsRNAs on detached wheat leaves significantly reduced lesion sizes; the independent dsRNA showed comparable effects on lesions with combination of two or three dsRNAs. Expression of three targets Chs7, Gls and Pkc was substantially down-regulated in Fg-infected wheat leaves. Further application of dsRNAs on wheat spikes in greenhouse significantly reduced infected spikelets. The identified RNAi constructs may be directly used for spray-induced gene silencing and stable expression in plants to control Fusarium pathogens in agriculture.